Kepastian Hukum Dokter Gigi dalam Menghadapi Tuduhan Malapraktik Pasca Berlakunya UU No. 17 Tahun 2023 - Erni Susanty Tahir; Aris Prio Agus Santoso; Aryono Aryono; Anindya Rizqita Salsabila (Jurnal Ilmu Kesehatan dan Gizi, 2026)
Malpractice in dental health services has become a complex legal issue as public awareness of service quality and patient rights continues to increase. The enactment of Law Number 17 of 2023 on Health introduces important changes in regulating the legal accountability of medical personnel, including dentists, particularly in relation to criminal liability for malpractice. This study analyzes the forms of dental malpractice and the criminal responsibility of dentists under the new Health Law. The research uses an empirical legal method with sociological and statutory approaches. Data were obtained through interviews and a review of relevant legislation, legal doctrines, and court decisions. The results show that dental malpractice can arise from negligence, failure to comply with professional standards, violations of standard operating procedures, and the absence or disregard of informed consent. Law Number 17 of 2023 stipulates that criminal liability for dentists can only be applied after a recommendation from the Professional Discipline Board, ensuring a clear distinction between inherent medical risks and professional misconduct. This framework is designed to provide balanced legal protection for both patients and dentists while strengthening legal certainty in malpractice case resolution. Consequently, dentists must understand professional standards and criminal liability mechanisms to practice responsibly and professionally.